Diagnostic value of immune indicators and cytokines in sepsis after percutaneous nephrolithotomy (PCNL): Immune indicators and cytokines in sepsis after PCNL - Jin, Yiheng; Li, Yamei; Zhang, Xiaoyu; Han, Bing; Yan, Xingshi (Journal of Medical Biochemistry, 2025)
Objective: To analyze the changes in and diagnostic value of immune indicators and cytokines in patients with sepsis after percutaneous nephrolithotomy (PCNL).Methods: Clinical information was gathered from 405 calculi patients who underwent PCNL at our facility between January 2021 and December 2024. The patients were divided into a sepsis group (12 patients) and a nonsepsis group (393 patients) on the basis of whether sepsis occurred after the operation. The levels of CD4+/CD8+ cells, the neutrophil-to-lymphocyte ratio (NLR), soluble trigger receptor-1 (sTREM-1) in myeloid cells, procalcitonin (PCT), tumor necrosis factor α (TNF-α), and interleukin-6 (IL-6) were measured in the two patient groups. The predictive value of the above indicators for sepsis was analyzed via receiver operating characteristic (ROC) curves.Results: The number of patients with staghorn calculi in the sepsis group was greater than that in the nonsepsis group (P
Keywords: Sepsis; Percutaneous nephrolithotomy; Cytokine; Immune indicators